New World Objects of Knowledge A Cabinet of Curiosities - Thurner, Mark; Pimentel, Juan (University of London Press, 2021)
From the late fifteenth century to the present day, countless explorers, conquerors, and other agents of empire have laid siege to the New World, plundering and pilfering its most precious artefacts and treasures. Today, these natural and cultural products-which are key to conceptualizing a history of Latin America-are scattered in museums around the world. With contributions from a renowned set of scholars, New World Objects of Knowledge delves into the hidden histories of forty of the New World's most iconic artifacts, from the Inca mummy to Darwin's hummingbirds. This volume is richly illustrated with photos and sketches from the archives and museums hosting these objects. Each artifact is accompanied by a comprehensive essay covering its dynamic, often global, history and itinerary. This volume will be an indispensable catalog of New World objects and how they have helped shape our modern world